Consumo alimentar de cálcio, fósforo, magnésio, proteínas e estado nutricional em mulheres hospitalizadas por fraturas osteoporóticas em um hospital universitário - Brondani, Juliana Ebling (2015)
Introduction: Currently, there is an increase in the life expectancy of the persons. It reflects the change in the epidemiological profile of the Brazilian population. Moreover, the biggest consequences faced due to this context is the increase in the prevalence of chronic comorbidities, among them, the osteoporosis. This pathology affects especially women in the post-menopause, and its main consequences are the fractures. They are responsible for an elevated morbidity and mortality that led to onerous treatments. On the other hand, nutrition represents an important role in the formation and maintenance of the bone mass. Considered now a part of the non-pharmacological treatment, a balanced alimentation, both in quality and quantity, probably will supply the necessary nutrients to maintain, at least in part, a regular bone health during the aging. Furthermore, it could be a possible protection factor for the main consequences of the osteoporosis in elderly. Objectives: to describe the alimentary consumption of calcium, phosphorus, magnesium, and proteins in women hospitalized for bone fractures in a service of Tertiary care at Rio Grande do Sul/RS. Methods: A case-control study was carried out at a university hospital. Women, 55 or older were invited to participate. Sixty-two women were recruited (42 women with fractures and 20 women without fractures). Information about clinical data and social history were recorded. An anthropometric evaluation was performed. A Questionnaire Quantitative of the Frequency of Foods (QQFA) to evaluate the ingestion of calcium, phosphorus, magnesium and proteins was applied. Results: the ingestion of calcium and magnesium was significant lower in women with fractures [446,9 mg/day vs. 689,90 mg/day and 135,49 mg/day vs.188,92 mg/day, respectively]. In the logistic regression analysis of fractures, high ingestion of calcium and magnesium were associated with a low odds of fracture. This result was adjusted for age and BMI. There were no differences in the protein and phosphorus intake between the groups. Conclusion: the studied women presented an ingestion of calcium and magnesium well below the current recommendations for sex and age group. Regarding the factors associated with the fracture, dietetic ingestion of calcium and magnesium they were considered as protectors against bone fractures.